A New Post-emergence Damping-off Disease of Eucalyptus Seedlings - Harsh, N. S. K.; Dadwal, V. S., Jamaluddin (Indian Forester, 1992)
A new post-emergence damping-off disease of Eucalyptus hybrid caused by Verticillium sp. has been reported and studied in detail. It is an internally seed borne disease causing as much as 80% mortality, of seedlings. The disease can be controlled by seed dip treatment for 5 min. In 0.2% solution of Topsin-M or Bavistion.